Laser Tracker - a handy device that verify proprioception of neck and head - Torbe, Dorota Anna; Torbe, Andrzej; Lubkowska, Anna (Journal of Education, Health and Sport, 2017)
Introduction:Cervical spine has the greatest mobility of the remaining part thereof. High mobility and relatively low load which is subject neck (own weight, the weight of the head, tension arising from the work of the shoulder girdle) make, it becomes vulnerable to injuries and overload resulting from adverse external conditions. Neck pain are a common problem of modern society, the sources of their formation can be many. According to many researchers, long-lasting neck pain interferes with afferent nerve conduction perpetuating abnormal muscle tension within the back of the head, neck and shoulder girdle, which adversely affects the feeling of proprioceptive cervical spine. Stability disorders may appear years before the onset of clinical symptoms, such as wypukliny or radiologically confirmed signs of degeneration of the intervertebral disc, significantly hindering the functioning of the patient and potentially reducing the maximum capabilities of the athlete. Aim: The aim of this paper is to present the possibility of using Laser Tracker, a simple, compact device intended for research and training in the deep sensation of the head and neck. Summary:In the light of the role that fully cervical posture for the entire body, and the fact that proper proprioception is the main pillar of prevention of injuries and overload control determines the correct neuromuscular therapy should help with visual feedback, which gives the opportunity to the Laser Tracker. In practice, the office seems to have a therapeutic effect on the invaluable role and unlimited possibilities of further use.